History matters: How short-term price charts hurt investment performance - Borsboom, Charlotte; Janssen, Dirk-Jan; Strucks, Markus; Zeisberger, Stefan (Journal of Banking & Finance, 2022)
When making investment decisions, people rely heavily on price charts displaying the past performance of an asset. Price charts can come with any time frame, which the provider might strategically choose. We analyze the impact of the time frame on retail investors’ behavior, particularly trading activity and risk-taking, in a controlled experiment with 1041 retail investors. We find that shorter time frames are associated with more trading activity, resulting in higher transaction fees and investor welfare losses. However, the time frame does not affect average risk-taking.